Pembuatan Design System Menggunakan Pendekatan Atomic Design dan A/B Testing - Kurniawan, Reyhan Adinata (Prodi Sistem Informasi Universitas Dharma Andalas, 2024)
The presence of digital products has become an integral part of human daily life. User Interface (UI) plays a central role in determining the success and adoption of products. Consistency and coherence in UI design are crucial to ensure users can easily understand and efficiently use products. However, creating a consistent UI, especially for complex digital products, is a formidable challenge. Hence, the Design System emerges as an innovative solution. From the perspective of user experience, consistency is considered a crucial factor that influences user ease in interacting with designs. This research aims to examine the implementation of atomic design and A/B testing approaches in creating a Design System, with a case study at Astra Buana Insurance company. It is expected that the findings of this research will contribute both theoretically and practically to the development of an effective and efficient Design System.